50 Years of Shoot! : Nostalgic Gems From the Top Footy Magazine - Published by Carlton Books (London Carlton Books, 2019)
In the magazine's 50th anniversary year, this book comprises a selection of page lifts from back issues of the magazine, featuring favourite weekly features, and stories and action photographs from the key issues of the day.
Include Color Illustrations
Keywords: Soccer